O STANDARYZACJI PRACY W OBSŁUDZE KLIENTA 1 PROCESACH ORGANIZACYJNEGO UCZENIA SIĘ - Woźniak, Jacek (Wydział Prawa i Administracji UAM, 2006)
Paul Lillrank, in his work The Quality o f Standard, Routine and Nonroutine Processes, considers the cause o f the gap between approaches to quality control in industry and the services to lie in the difference between standard and non-routine processes. The primary cause of this discrepancy lies in the category of “interpretation” , which is used in non-routine processes to signify the use of new criteria (created basing on concrete cases) for classification. Dividing the various kinds of service environments into three categories allows us to see the drawbacks of Lillrank’s differentiation. Lillrank’s paradigmatic example (qualifying for surgery) is a specific example of a professional service combining management o f emotions and management of procedural innovation. The model o f three spheres in which services are performed seems to give a better insight into the issue of “interpretation” in the service area, as it enables differentiating interpretation of facts and interpretation of emotions. It enables us to formulate the conditions under which organizational learning takes place, and to show the areas in which the organization refuses to analyse non-routine processes.
THE STANDARISATION OF CLIENT SERVICE AND PROCESSES OF ORGANISATION LEARNING